Femtosecond laser micro-patterning of optical properties and functionalities in novel photosensitive silver-containing fluorophosphate glasses - de Castro, Tarcio [UNESP]; Fares, Hssen [UNESP]; Khalil, Alain Abou; Laberdesque, Romain; Petit, Yannick; Strutinski, Clément; Danto, Sylvain; Jubera, Véronique; Ribeiro, Sidney J.L. [UNESP]; Nalin, Marcelo [UNESP]; Cardinal, Thierry; Canioni, Lionel (Elsevier, 2019)
Silver-containing glasses are promising candidates for photonic applications, due to the potentiality of spectroscopic properties of silver nanoclusters (NC's)and/or silver metallic nanoparticles. In this framework, silver-containing fluorophosphate glasses are candidates with a strong potential. Indeed, combined with femtosecond laser irradiation, silver NC's may be tailored in three-dimensional fluorescent micro-structures, whose spectroscopic properties have been investigated, revealing the creation of silver NC's but also of NP's during laser irradiation in the studied fluorophosphate glass. Additionally, the photo-inscription of silver NC's is correlatively accompanied by a positive index change, which has led to the demonstration of optical waveguiding behavior. Finally, the management of the reservoir of available silvers for laser inscription is investigated. Unlike previous observations made in standard oxide phosphate glasses, the considered silver-containing fluorophosphate glass exhibes an intriguing ability to be re-written when subjected to successive overlapping laser irradiations. Upon the optimization of compositions with tailored photo-sensitivity, the re-writable ability of fluorophosphate glasses paves the way to the design of advanced photonic devices such as photonic optical circuits, evanescent sensors or 3D high-density optical data storage.
Keywords: Femtosecond laser inscription; Fluorescent silver clusters; Fluorophosphate glasses; Integrated waveguides; Multiscale photonic architectures; Plasmonic nanoparticles